Waiting for spring. 4 - Anashin, 1992- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
"The preliminary games begin, and Tawa and the squad are all fired up! Mitsuki's childhood best friend Aya-chan, is also at the arena playing his best, and the stakes are high. As Mitsuki and Reina cheer on the Seiryo team, Mitsuki sees the boys sweep the floor and is inspired to work hard too! But when a ref's whistle cuts through the air, a close friend lies injured on the court..." --Back cover.